An evaluation of demand and capacity planning processes – a qualitative case study on completely-knocked-down vehicles at Mercedes-Benz Cars - Chemendy, Natascha (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCom)--Stellenbosch University, 2018.